Peran Guru dalam Meningkatkan Motivasi dan Prestasi Belajar Siswa Sekolah Dasar - Yumriani, Yumriani; Maemunah, Maemunah; Samsuriadi, Samsuriadi; Tapa, Muh Asri; Burbakir, Burbakir (Pedagogik Journal of Islamic Elementary School, 2022)
This study aims, to determine the factors that support the achievement of student achievement in elementary schools in terms of the teacher's role. This research was conducted at the Inpres Pattallassang Elementary School. The type of research used is descriptive qualitative research with the aim of describing the teacher's role in increasing student motivation and learning achievement at the elementary school education level. Data collection was carried out using semi-structured interviews and observation. The fundamental thing in qualitative research is the researcher as an instrument. Therefore, in research, data analysis will be carried out from the time this research takes place to data collection to the preparation of research reports that become the object or target of research in the field. For qualitative data analysis, a sequence of analytical activities is carried out in stages, namely the process of data reduction, data presentation, drawing conclusions, and verifying information into statements. The results of the study reveal that teachers have a very important role in student motivation and achievement such as being a demonstrator, class managers, mediators, facilitators, evaluators, and motivators for students so that students can achieve their learning achievements.